Analisis Tahapan Produksi Film sebagai Dasar Penciptaan Karya Sinematografi - Alhanuna Najmal Abidah; Moh. Amin (CV. ITTC INDONESIA, 2026)
This study aims to analyze the stages of film production as the foundation for creating high-quality cinematographic works. Film production is a complex and systematic process involving several interconnected stages, namely pre-production, production, and post-production. Each stage plays a significant role in determining the success of a film, both in terms of technical execution, artistic quality, and the effective delivery of messages to audiences. This research employed a descriptive qualitative method using a library research approach. The data were collected from various academic sources, including books, scientific journals, articles, and other relevant literature related to film production management and cinematography. The findings indicate that the pre-production stage serves as the primary foundation for planning a film through idea development, scriptwriting, budgeting, casting, and technical preparation. The production stage involves the implementation of all planned activities through the filming process while managing both artistic and technical aspects. Furthermore, the post-production stage focuses on refining the film through video editing, sound editing, visual effects, music scoring, and distribution. Therefore, the success of a cinematographic work depends on the integration and effective management of every stage of film production, resulting in audiovisual works with strong technical quality, aesthetic value, and effective communication.